Racial attitudes of the mid 20th century Britain as reflected in "Ten Little Niggers" by Agatha Christie - Neffová, Lucie (Univerzita Pardubice, 2014)
The aim of this bachelor thesis is to analyse racial attitudes of the mid 20th century Britain as they are reflected in the novel Ten Little Niggers by Agatha Christie. Firstly, the theoretical part deals with historical development of race and racism, particularly in Britain, and focuses on historical periods, which were crucial for evolving racial and ethnic attitudes such as slavery, colonization or immigration. Further, the field of cultural studies is introduced as an approach to an analysis of literary works and also various theories about race and racism in literature, mainly in detective fiction, are presented. The application of the theory is shown on the analysis of specific situations and characters from the novel Ten Little Niggers as well as from other similar works of the same period written by Agatha Christie.
Rasové postoje v Británii v polovině 20. století zobrazené v románu Agathy Christie "Deset malých černoušků"
Keywords: Ten Little Niggers; Christie, Agatha; racism; attitudes; Britain; analysis; detective fiction; Deset malých černoušků; Christie, Agatha; rasismus; postoje; Británie; analýza; detektivní literatura